Influence of strains and defects on ferroelectric and dielectric properties of thin-film barium-strontium titanates - Balzar, D.; Ramakrishnan, P. A.; Spagnol, P.; Mani, S.; Hermann, A. M.; Matin, M. A. (Japan Soc Applied Physics, 2002)
Pristine, W and Mn 1% doped Ba(0.6)Sr(0.4)TiO(3) epitaxial thin films grown on the LaAlO(3) substrate were deposited by pulsed laser deposition (PLD). Dielectric and ferroelectric properties were determined by the capacitance measurements and X-ray diffraction was used to determine both residual elastic strains and defect-related inhomogeneous strains-by analyzing diffraction line shifts and line broadening, respectively. We found that both elastic and inhomogeneous strains are affected by doping. This strain correlates with the change in Curie-Weiss temperature and can qualitatively explain changes in dielectric loss. To explain the experimental findings, we model the dielectric and ferroelectric properties of interest in the framework of the Landau-Ginzburg-Devonshire thermodynamic theory. As expected, an, elastic-strain contribution due to the epilayer-substrate misfit has an important influence on the free-energy. However, additional terms that correspond to the defect-related inhomogeneous strain had to be introduced to fully explain the measurements.
Keywords: ferroelectric thin films; strain; defects; Curie-Weiss temperature; barium-strontium titanate